Elastic stress coupling between supraglacial lakes - Stevens, L; Das, S; Behn, M; McGuire, J; Lai, C-Y; Joughin, I; Larochelle, S; Nettles, M (American Geophysical Union, 2024)
Supraglacial lakes have been observed to drain within hours of each other, leading to the hypothesis that stress transmission following one drainage may be sufficient to induce hydro-fracture-driven drainages of other nearby lakes. However, available observations characterizing drainage-induced stress perturbations have been insufficient to evaluate this hypothesis. Here, we use ice-sheet surface displacement observations from a dense global positioning system array deployed in the Greenland Ice Sheet ablation zone to investigate elastic stress transmission between three neighboring supraglacial lake basins. We find that drainage of a central lake can place neighboring basins in either tensional or compressional stress relative to their hydro-fracture scarp orientations, either promoting or inhibiting hydro-fracture initiation beneath those lakes. For two lakes located within our array that drain close in time, we identify tensional surface stresses caused by ice-sheet uplift due to basal-cavity opening as the physical explanation for these lakes’ temporally clustered, hydro-fracture-driven drainages and frequent triggering behavior. However, lake-drainage-induced stresses in the up-flowline direction remain low beyond the margins of the drained lakes. This short stress-coupling length scale is consistent with idealized lake-drainage scenarios for a range of lake volumes and ice-sheet thicknesses. Thus, on elastic timescales, our observations and idealized-model results support a stress-transmission hypothesis for inducing hydro-fracture-driven drainage of lakes located within the region of basal cavity opening produced by the initial drainage, but refute this hypothesis for distal lakes.